High input impedance DC servo loop circuit - Spinelli, Enrique Mario (2014)
technique, used to reject spurious DC components and thus allow centring of the signal between the power supply rails and exploitation of all the available voltage range. A generic DC servo loop that presents high input impedance and can work as a front-end is proposed. It is designed to be implemented with standard operational amplifiers, to offer solutions for ?board level? analogue instrumentation design. The main features of the circuit are analysed, and analytical expressions are provided for its adaptation for solving different instrumentation problems.